Factors Affecting the Organizational Commitment of Nurses in Comprehensive Health Services: A Systematic Review - Erfan Rofiqi; Rahayu Tri Nuritasari; Pipit Festi Wiliyanarti (Universitas Airlangga, 2019)
Introduction: Organization commitment is an important variable in understanding employee behavior that has a serious effect on organizational performance. Employees not only have to have expertise, empowerment and competence, but they also have to have organizational commitment. Therefore, the level of attachment and commitment of the nurses to their organization can influence their clinical competence. The research was conducted to identify the factors that influence nursing organizational commitment.Methods: The literature review employed the Scopus, ScienceDirect, Pubmed, Ebsco and CINAHL databases to retrieve original articles published between 1999 and 2017. The method used to arrange the literature review started with the topic selection and then the reviewer determined the following keywords: organization commitment, commitment, nursing, health and factors of commitment. Out of the 2.134 articles found, there were 15 journals with a cross-sectional study design that discussed the organizational commitment of nurses.Results: The organizational commitment of care is influenced by many factors, both internal and external. These factors include leadership style, compensation, career development, organizational culture /climate, spiritual health and learning organizations.Conclusion: The factors found above can increase the commitment of nurse organizations in comprehensive health services.